2020
DOI: 10.14744/tjtes.2019.86717
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasonography and Scoring Systems: The Effect on the Negative Appendectomy Rate and Gender

Abstract: BACKGROUND: Despite the development of clinical, laboratory, and imaging methods, the diagnosis of acute appendicitis is not always easy, and negative appendectomy rates are still high. This study aims to reveal the effects of different scoring systems on the diagnostic accuracy of acute appendicitis and negative appendectomy rates, alone or when evaluated together with ultrasonography. METHODS: In this study, 202 consecutive patients who underwent emergency appendectomy for acute appendicitis were included. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
11
2
Order By: Relevance
“…Specificity of RIPASA score in the current study was 75% which matched with the results of Odzemeir et al [19] and Akbar et al [15] . However, it was much higher than those reported by Dezfuli et al [20] and Şenocak et al [21] who reported 46.5% and 37.5 %, respectively, and this is assumed to be due to large number of false negative cases reported in their study also it was less than what reported by Korkut et al 18] , who reported 99.7 % specificity and this can be explained by higher cut-off value in their study which was 12.…”
Section: Discussioncontrasting
confidence: 64%
“…Specificity of RIPASA score in the current study was 75% which matched with the results of Odzemeir et al [19] and Akbar et al [15] . However, it was much higher than those reported by Dezfuli et al [20] and Şenocak et al [21] who reported 46.5% and 37.5 %, respectively, and this is assumed to be due to large number of false negative cases reported in their study also it was less than what reported by Korkut et al 18] , who reported 99.7 % specificity and this can be explained by higher cut-off value in their study which was 12.…”
Section: Discussioncontrasting
confidence: 64%
“…Despite the relatively high incidence of needless appendectomies, ranging from 20% to 30%, such occurrences are deemed tolerable given the substantial reliability of beneficial outcomes. 8,9 The current study unveiled the presence of diagnostic markers in acute appendicitis.…”
Section: Introductionmentioning
confidence: 68%
“…Due to the reliability of positive values, needless appendectomies (20-30%) are permissible. [5][6][7] Delaying diagnosis and treatment can result in gangrene perforation and diffuse peritonitis. This makes radiological examinations easy to carry out with good sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%